Conditioning Solid-State Anode-Less Cells for the Next Generation of Batteries - Manuela C. Baptista; Beatriz Moura Gomes; Diana Capela; Miguel F. S. Ferreira; Diana Guimarães; Nuno A. Silva; Pedro A. S. Jorge; José J. Silva; Maria Helena Braga (Batteries, 2023)
Anode-less batteries are a promising innovation in energy storage technology, eliminating the need for traditional anodes and offering potential improvements in efficiency and capacity. Here, we have fabricated and tested two types of anode-less pouch cells, the first using solely a copper negative current collector and the other the same current collector but coated with a nucleation seed ZnO layer. Both types of cells used the same all-solid-state electrolyte, Li2.99Ba0.005ClO composite, in a cellulose matrix and a LiFePO4 cathode. Direct and indirect methods confirmed Li metal anode plating after charging the cells. The direct methods are X-ray photoelectron spectroscopy (XPS) and laser-induced breakdown spectroscopy (LIBS), a technique not divulged in the battery world but friendly to study the surface of the negative current collector, as it detects lithium. The indirect methods used were electrochemical cycling and impedance and scanning electron microscopy (SEM). It became evident the presence of plated Li on the surface of the current collector in contact with the electrolyte upon charging, both directly and indirectly. A maximum average lithium plating thickness of 2.9 µm was charged, and 0.13 µm was discharged. The discharge initiates from a maximum potential of 3.2 V, solely possible if an anode-like high chemical potential phase, such as Li, would form while plating. Although the ratings and energy densities are minor in this study, it was concluded that a layer of ZnO, even at 25 °C, allows for higher discharge power for more hours than plain Cu. It was observed that where Li plates on ZnO, Zn is not detected or barely detected by XPS. The present anode-less cells discharge quickly initially at higher potentials but may hold a discharge potential for many hours, likely due to the ferroelectric character of the electrolyte.